The Cultural Pluralism Reflected in Language Choice (A case study of Girl dormitory of Nurul Huda) - Ainur Rohmah; Ummu Mulkiyah (Channing : Journal of English Language Education and Literature, 2021)
This study aims to find out the language choice that is used by students (santri) in the girl dormitory (asrama putri)Nurul Huda Sukaraja OKU Timur and factors that support using these languages. This study is an ethnography that belongs to qualitative research. In this study, the researcher has a role as an instrument to collect the data. The data are collected through observation and field notes toward utterances produced by students in their daily life communication. The result shows that there are some kinds of language used by students in the girl dormitory. They are standard Indonesian and nonstandard Indonesian language, Javanese kromo and Javanese ngoko and Komering. Each language has its situation to be used by all students. And most of the students use nonstandard Indonesian and Javanese ngoko in most of the daily life communication.